2021
DOI: 10.1002/jpln.202000475
|View full text |Cite
|
Sign up to set email alerts
|

Substrate quality of drained organic soils—Implications for carbon dioxide fluxes

Abstract: Background Peatlands only cover a minor fraction of the global terrestrial surface, but due to drainage, they are major contributors to carbon dioxide (CO2) emissions from soils. Previous studies have shown that hydrological conditions, nutrient availability and anthropogenic disturbance play an important role in the mineralisation of organic matter. Furthermore, microbial turnover depends on peat quality, which is determined by its botanical origin and degree of transformation under natural conditions. Aims T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 68 publications
1
1
0
1
Order By: Relevance
“…Incubation studies with sieved, air-dried samples (7.6-52.6% OC) indicated that the susceptibility of OC to mineralisation increased with decreasing OC content in German organic soils 26 and similar results were reported for Finnish soils (3.1-49.4% OC) incubated under anoxic and physically disturbed conditions 27 . The present results, obtained with structurally intact organic soils, support the possibility of positive feedback whereby organic soils in advanced stages of decomposition (i.e., with low OC content) may show an increased mineralisation rate 26,33,34 . However, other studies have emphasised the importance of OC quality and intrinsic decomposability for rates of CO 2 emission with the assumption that lower rates would be maintained by soils in advanced stages of decomposition, where the more easily decomposed fractions would already be depleted [35][36][37] .…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Incubation studies with sieved, air-dried samples (7.6-52.6% OC) indicated that the susceptibility of OC to mineralisation increased with decreasing OC content in German organic soils 26 and similar results were reported for Finnish soils (3.1-49.4% OC) incubated under anoxic and physically disturbed conditions 27 . The present results, obtained with structurally intact organic soils, support the possibility of positive feedback whereby organic soils in advanced stages of decomposition (i.e., with low OC content) may show an increased mineralisation rate 26,33,34 . However, other studies have emphasised the importance of OC quality and intrinsic decomposability for rates of CO 2 emission with the assumption that lower rates would be maintained by soils in advanced stages of decomposition, where the more easily decomposed fractions would already be depleted [35][36][37] .…”
Section: Resultssupporting
confidence: 74%
“…https://doi.org/10.1038/s43247-024-01459-8 phenolics, were not found to be enriched in drained organic topsoils under agriculture in Germany 33 , and simple chemical characteristics of OC as proxies for biochemical decomposability were unable to explain the variability in CO 2 emissions in a comprehensive study of drained organic soils in Switzerland 25 . In summary, the role of OC quality needs to be further clarified, but the present data do suggest that the remaining OC content as such is not a strong predictor of area-scaled CO 2 emission rates (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Incubation studies with sieved, air-dried samples (7.6-52.6% OC) indicated that the susceptibility of OC to mineralisation increased with decreasing OC content in German organic soils 7 and similar results were reported for Finnish soils (3.1-49.4% OC) incubated under anoxic and physically disturbed conditions 8 . The present results, obtained with structurally intact organic soils, support the possibility of a positive feedback whereby organic soils in advanced stages of decomposition (i.e., with low OC content) may show an increased mineralisation rate 7,33,34 . However, other studies have emphasised the importance of OC quality and intrinsic decomposability for rates of CO2 emission with the assumption that lower rates would be maintained by soils in advanced stages of decomposition, where the more easily decomposed fractions would already be depleted [35][36][37] .…”
Section: Soil Weight-and Oc-specific Emissionssupporting
confidence: 74%
“…Journal of Soils andSediments, 18, 2500-2510. https Peatlands cover about 3% of the global terrestrial surface (Xu et al, 2018) and store around 598 Pg carbon (C), which represents about 21% of the global soil organic C sock estimated to 2800 Pg C (Leifeld and Menichetti, 2018;Jackson et al, 2017). Around 13% of the world's peatlands have been drained for agriculture, forestry or peat extraction (Säurich et al, 2021), turning peatlands from C sinks or near C neutrality into major C sources. Under current circumstances, i.e.…”
Section: Dedicationmentioning
confidence: 99%